Metabolic Reprogramming in SARS-CoV-2 Infection Impacts the Outcome of COVID-19 Patients - Martínez-Gómez, Laura E.; Ibarra-González, Isabel; Fernández-Lainez, Cynthia; Tusie, Teresa; Moreno-Macías, Hortensia; Martinez-Armenta, Carlos; Jimenez-Gutierrez, Guadalupe Elizabeth; Vázquez-Cárdenas, Paola; Vidal-Vázquez, Patricia; Ramírez-Hinojosa, Juan P.; Rodríguez-Zulueta, Ana P.; Vargas-Alarcón, Gilberto; et al. (Frontiers in Immunology, 2022)
Introduction: Severe acute respiratory syndrome–coronavirus 2 (SARS-CoV-2) infection triggers inflammatory clinical stages that affect the outcome of patients with coronavirus disease 2019 (COVID-19). Disease severity may be associated with a metabolic imbalance related to amino acids, lipids, and energy-generating pathways. The aim of this study was to characterize the profile of amino acids and acylcarnitines in COVID-19 patients. A multicenter, cross-sectional study was carried out. A total of 453 individuals were classified by disease severity. Levels of 11 amino acids, 31 acylcarnitines, and succinylacetone in serum samples were analyzed by electrospray ionization–triple quadrupole tandem mass spectrometry. Different clusters were observed in partial least squares discriminant analysis, with phenylalanine, alanine, citrulline, proline, and succinylacetone providing the major contribution to the variability in each cluster (variable importance in the projection >1.5). In logistic models adjusted by age, sex, type 2 diabetes mellitus, hypertension, and nutritional status, phenylalanine was associated with critical outcomes (odds ratio=5.3 (95% CI 3.16-9.2) in the severe vs. critical model, with an area under the curve of 0.84 (95% CI 0.77-0.90). In conclusion the metabolic imbalance in COVID-19 patients might affect disease progression. This work shows an association of phenylalanine with critical outcomes in COVID-19 patients, highlighting phenylalanine as a potential metabolic biomarker of disease severity.